1995
DOI: 10.1056/nejm199511233332101
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenicity of High Vitamin A Intake

Abstract: High dietary intake of preformed vitamin A appears to be teratogenic. Among the babies born to women who took more than 10,000 IU of preformed vitamin A per day in the form of supplements, we estimate that about 1 infant in 57 had a malformation attributable to the supplement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
255
1
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 640 publications
(266 citation statements)
references
References 19 publications
3
255
1
7
Order By: Relevance
“…Excess retinoid signaling can cause multiple developmental toxicities in various animals including humans (Rothman et al 1995;Mulder et al 2000;Degitz et al 2003). To our knowledge, only Gardiner et al (2003) have detected RAR agonistic activity in water samples, which they collected from a lake in Minnesota and a pond in California where frog malformations were routinely found; however, the causative contaminants, named as ''environmental retinoids'', were not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Excess retinoid signaling can cause multiple developmental toxicities in various animals including humans (Rothman et al 1995;Mulder et al 2000;Degitz et al 2003). To our knowledge, only Gardiner et al (2003) have detected RAR agonistic activity in water samples, which they collected from a lake in Minnesota and a pond in California where frog malformations were routinely found; however, the causative contaminants, named as ''environmental retinoids'', were not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Our data demonstrate that both RA and TGF-[~ inhibit the expression of Msx-1 mRNA in palate cells, and that a synergistic effect is manifested when ceils are treated simuhaneousty with both agents. Retinoic acid is a potent cleft palate-inducing teratogen in some strains of mice and is a known human teratogen (19,21,36). RA inhibits palate mesenchymal cell proliferation and prevents differentiation of palatal medial edge epithelial cells (1,43).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A is an essential agent for vision, embryogenesis, reproduction, the integrity of membrane structures, epithelial differentiation, growth, and development. 51,52 Epidemiologic studies have shown a reduced risk of various chronic diseases, particularly cancers of lung, gastrointestinal tract, bladder, breast and pancreas and cardiovascular disease with dietary consumption of various carotenoids. [53][54][55][56][57][58][59][60][61] However, randomized clinical trials have not shown any consistent reduction in the incidence of cancers or cancer deaths, or of cardiovascular disease.…”
Section: Vitamin a (Retinol) And Beta-carotenementioning
confidence: 99%